Effectiveness of Indigenously Prepared Punica Granatum and Camellia Sinesis Mouthwashes as an adjunct to Non Surgical Periodontal Therapy: A Clinical Trial - Champaneri, Harshal Rajeshbhai; Yadav, Nirma; Makhijani, Barkha; Shetty, Neema; Mathur, Aditi; Manohar, Balaji (Journal of Nepalese Society of Periodontology and Oral Implantology, 2017)
Background: Chronic periodontitis is a bacterially induced chronic disease that is immune-inflammatory in nature. The incidence and progression of this disease is related to a substantial increase in gram negative anaerobic rods. The use of antimicrobial mouthwashes as an adjunct to mechanical plaque control is well established in dental practice. Punica granatum and Camellia sinesis extract are naturally occurring antimicrobial agents. The active ingredient in Punica granatum and Camellia sinesis is polyphenolic flavonoid, which is an antioxidant in nature. It inhibits the production of arachidonic acid metabolites such as pro- inflammatory prostaglandins and leukotriens, resulting in a decreased inflammatory response. Aim: To evaluate the efficacy of indigenously prepared Punica granatum and Camellia sinesis mouthwashes to the commercially available chlorhexidine mouthwash. Materials and Methods: Thirty subjects diagnosed with chronic generalized marginal gingivitis were selected and randomly divided into three groups. Group 1 – Camellia sinesis mouthwash group, Group 2 – Punica granatum mouthwash group and Group 3 – Chlorhexidine mouthwash group. Subjects were instructed to use the prescribed mouthwash for 14 days. Plaque index, gingival index and calculus component of periodontal index were recorded at baseline and at 14 days. Results: The clinical study observed significant improvement in plaque and gingival status at all sites (p<0.05). Camellia sinesis and Punica granatum mouthwash showed significant improvement in plaque, gingival and calculus score. Conclusion: Camellia sinesis and Punica granatum mouthwash are beneficial in improving gingival status due to its profound styptic action, with sufficient reduction in plaque scores.